Economic feasibility of large scale PV water pumping applications utilizing real field data for a case study in Jordan - Ibrahim Odeh (International Journal of Renewable Energy Development, 2014)
Economic viability of photovoltaic, diesel and grid connected water pumping systems is investigated and compared for system capacities in the range 1500 m4/day to 100,000 m4/day. Actual performance data from installed systems are considered in calculating systems outputs for base case scenarios. Sensitivity analysis is carried out to generalize results for other locations and conditions. Several scenarios of the effect of variation electricity tariffs, components prices, diesel fuel prices, operation cost and interest rate on the output water unit cost (US$/1000m4)  are investigated.  Breakeven points of PV pumping systems are determined at certain input parameters.